Influence of the actual weather situation on non-CO2 aviation climate effects: The REACT4C Climate Change Functions - Frömming, Christine; Grewe, Volker; Brinkop, Sabine; Jöckel, Patrick; Haslerud, Amund S.; Rosanka, Simon; van Manen, Jesper; Matthes, Sigrun (Copernicus Publications, 2020)
The influence of different weather situations on non-CO2 aviation climate impact is investigated. The aim is to identify systematic weather related sensitivities. If aircraft trajectories avoid the most sensitive areas, the overall climate impact might be reduced. An enhanced significance of the position of emission release is identified in relation to high pressure systems, in relation to the jet stream, in relation to polar night, and in relation to the altitude of the tropopause. The results of this study represent a comprehensive dataset for studies aiming at weather dependent flight trajectory optimization reducing total climate impact.